PENGARUH PERSEPSI DAN SIKAP PELAKU USAHA TERHADAP PEMILIHAN BANK SYARIAH SETELAH FATWA MAJELSI ULAMA INDONESIA DI KAUMAN SURAKARTA - Ilmawan, Nova Firnia (El-Hayah, 2017)
Abstract : Indonesian Ulama Council (MUI) issued a fatwa on bank interest and the prohibition of transaction with the conventional banks in early 2004. After the MUI fatwa, both types of banks are still recorded growth in all sectors of performance, there is no massive diversion of funding from conventional banks to Islamic banks. One of the factors that shape consumers behavior in their decision is a psychological factor consisting of perceptions and attitudes. This study aims to determine the influence of 1). Perception, 2). Attitude, 3). Perceptions and attitudes of business actors in Kauman Surakarta after MUI fatwa against the selection of sharia banks.This research uses quantitative descriptive approach. The research located in Kauman Surakarta was conducted in May-June 2017. The research population was 284 business actors with a sample size of 181 subjects. Sampling sampling method using fixed disease sampling. Respondents' data were collected using questionnaires. The dependent variable of research is the selection of syariah bank. Independent variables of research are perceptions and attitudes. Test the validity of perceptual variables, attitudes and selection of sharia banks using Corrected Item-Total Correlationmore than 0.35. The reliability test used Cronbach's Alpha value with the values of 0.841 perceptions, 0.922 attitudes and 0.957 election of sharia banks. Data analysis using multiple logistic regression.The results obtained 1). Perceptions affect the selection of Bank Syariah with Wald 24,328 test value significant at 0,000 (more or less0.05) 2). Attitudes affecting the selection of sharia banks with Wald 28,115 test value significant at 0,000 (more or less0.05) 3). Perceptions and attitudes affect the selection of sharia banks with the results of the simultaneous test (Omnibus Tests of Model Coefficients) 96.359 significant at 0.000 (more or less0.05). Prediction analysis on result of research is equal to 1,999 perception and 1,987 for attitude where equation formula in multiple logistic regression is Y = 40.055 + 1.999 X1 + 1.987 X2.Keywords: Perception, Attitude, Selection of  shariah Bank, MUI Fatwa, Multiple Logistic Regression.